Improving IF Algorithm for Data Aggregation Techniques in Wireless Sensor Networks - Madhav Ingle; PVRD Prasada Rao (Institute of Advanced Engineering and Science, 2018)
In Wireless Sensor Network (WSN), fact from different sensor nodes is collected at assembling node, which is typically complete via modest procedures such as averaging as inadequate computational power and energy resources. Though such collections is identified to be extremely susceptible to node compromising attacks. These approaches are extremely prone to attacks as WSN are typically lacking interfere resilient hardware. Thus, purpose of veracity of facts and prestige of sensor nodes is critical for wireless sensor networks. Therefore, imminent gatherer nodes will be proficient of accomplishment additional cultivated data aggregation algorithms, so creating WSN little unresisting, as the performance of actual low power processors affectedly increases. Iterative filtering algorithms embrace inordinate capacity for such a resolution. The way of allocated the matching mass elements to information delivered by each source, such iterative algorithms concurrently assemble facts from several roots and deliver entrust valuation of these roots. Though suggestively extra substantial against collusion attacks beside the modest averaging techniques, are quiet vulnerable to a different cultivated attack familiarize. The existing literature is surveyed in this paper to have a study of iterative filtering techniques and a detailed comparison is provided. At the end of this paper new technique of improved iterative filtering is proposed with the help of literature survey and drawbacks found in the literature.